2019
DOI: 10.1029/2019ja026544
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Semiannual Oscillations of Thermospheric Composition in TIMED/GUVI Limb Measurements

Abstract: The Global UltraViolet Imager (GUVI) onboard the Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite provides a data set of vertical thermospheric composition (O, N 2 , and O 2 densities) and temperature profiles from 2002-2007. Even though GUVI sampling is limited by orbital constraint, we demonstrated that the GUVI data set can be used to derive the altitude profiles of the amplitudes and phases of annual oscillation (AO) and semiannual oscillation (SAO), thereby providing important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 64 publications
6
53
2
Order By: Relevance
“…The hemispheric asymmetry of annual variations in amplitudes (A 12 ) and phases (F 12 ) shown in Figures 5 and 6 may be associated with the hemispheric differences in the tides and waves originating in the lower atmosphere, which are probably due to different land and ocean distributions in the NH and SH. This may also result from hemispheric differences in the geomagnetic field configuration (Lei et al, 2013; Qian et al, 2009; Yue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The hemispheric asymmetry of annual variations in amplitudes (A 12 ) and phases (F 12 ) shown in Figures 5 and 6 may be associated with the hemispheric differences in the tides and waves originating in the lower atmosphere, which are probably due to different land and ocean distributions in the NH and SH. This may also result from hemispheric differences in the geomagnetic field configuration (Lei et al, 2013; Qian et al, 2009; Yue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…O/N 2 are calculated using the O and N 2 altitude profiles. Meanwhile, we transform the altitude profiles to pressure levels using the observed profiles of O, N 2 , and O 2 number densities and temperature based on the ideal gas law (Yue et al, 2019). The O/N 2 on different constant pressure levels are calculated, corresponding to the logarithm of pressure (log P) values from −13.5 to −6 with a step width of 0.5, namely, 16 constant pressure surfaces.…”
Section: Instrument and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Stephan et al () also found them in strong agreement during a geomagnetic storm. Yue et al () demonstrated their consistent seasonal variations from GUVI limb and disk ∑O/N2 during geomagnetically quiet periods. Emmert et al () presented the first validation of mass density from GUVI limb retrievals by comparing with that from satellite orbit data.…”
Section: Introductionmentioning
confidence: 89%